“Everything has already happened!”: the first Russian translation of the poem by Paul Henry Gerber - Lada V. Syrovatko (Слово.ру: балтийский акцент)
The paper is the first translation into Russian of the poem ‘Everything has already happened! (Epistle to Julius Stettenheim)’ by the outstanding German scholar, professor at the University of Königsberg, medical practitioner and poet Paul Henry Gerber (1863—1919). The poem first appeared in Gerber’s collection of poems ‘From Youth. Songs and Poetry’ (Berlin, 1895); it was also reprinted in a review of the book published in the journal Mnemosyne. The poem, in which gentle humour shades into deep philosophical content, was addressed to the German publisher and journalist Julius Stettenheim, and contains allusions to the Book of Ecclesiastes and the works of the German classics. The publication also reproduces the original text and a translation of a journal review. The commentary briefly covers the principles of translation, and provides information on the main motifs of the poem and the personalities mentioned in it.